1.86=6.2a

Simple and best practice solution for 1.86=6.2a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.86=6.2a equation:


Simplifying
1.86 = 6.2a

Solving
1.86 = 6.2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6.2a' to each side of the equation.
1.86 + -6.2a = 6.2a + -6.2a

Combine like terms: 6.2a + -6.2a = 0.0
1.86 + -6.2a = 0.0

Add '-1.86' to each side of the equation.
1.86 + -1.86 + -6.2a = 0.0 + -1.86

Combine like terms: 1.86 + -1.86 = 0.00
0.00 + -6.2a = 0.0 + -1.86
-6.2a = 0.0 + -1.86

Combine like terms: 0.0 + -1.86 = -1.86
-6.2a = -1.86

Divide each side by '-6.2'.
a = 0.3

Simplifying
a = 0.3

See similar equations:

| 25x^3-15x^4=5x^3 | | -30+5(x-2)=4x+7 | | 9-7x=42+(-4x) | | 3x^2-58x-40=0 | | 3ab-2b=3a-b | | -3x^2-3x+90=0 | | 1.2y-0.3x=0.12 | | -7x-5y=11 | | X/11=-22 | | f(x)=2x^2-16x+27 | | 3Y-9-3Y=-9 | | 1.2x-0.3y=0.12 | | 12-7x=9x-5x-87 | | 4x^3+72x^2+68x=0 | | 5/6-x/6=6/5 | | 2^3*x=1/64 | | 3x-5x+4-x+7=88 | | -3x+8=5x-2 | | -x^3+10x^2+39x=0 | | 3x-7=3(x-3)+3 | | ln(x+5)=ln(x-4)-ln(x+4) | | a-1/2=2a-2/3 | | 4x+15x+6=3x-14 | | 19+20m+m^2= | | 24x+8x^2+2x^3=0 | | .4w-.3w+.4w=3 | | 3(2x-5)=5(x-4+x) | | 9c^3+12c^2=0 | | 4x^3-48x^2+140x=0 | | 100/10= | | 5(7x+1)=320 | | 3x+2x+3+5x-13=180 |

Equations solver categories